2015
DOI: 10.1002/ejlt.201400557
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of polymorphic transition of cocoa butter and cocoa butter equivalent by addition of d‐limonene

Abstract: The essential oils obtained from citric fruits have been used as aromatizing agents in various foods. However, the addition of orange essential oil, D-limonene, to cocoa butter (CB) has been shown to have an influence on its crystallization behavior. The objective of this study was to evaluate the influence of adding D-limonene at concentrations of 1.5 and 5% w/w on the polymorphic transitions in Brazilian CB and in a commercial cocoa butter equivalent (CBE). X-ray diffraction (XRD) was used to identify the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Furthermore, limonene also affects the polymorphic forms during storage, with the general observation that limonene accelerates polymorphic transitions during 4 weeks of storage . This observation was confirmed by Miyasaki et al, who studied the effect of limonene on the crystallization behavior of a cocoa butter equivalent and Brazilian cocoa butter. Interestingly, their results also demonstrated a concentration effect with a more pronounced effect for 5% than for 1.5% limonene …”
Section: Introductionmentioning
confidence: 61%
“…Furthermore, limonene also affects the polymorphic forms during storage, with the general observation that limonene accelerates polymorphic transitions during 4 weeks of storage . This observation was confirmed by Miyasaki et al, who studied the effect of limonene on the crystallization behavior of a cocoa butter equivalent and Brazilian cocoa butter. Interestingly, their results also demonstrated a concentration effect with a more pronounced effect for 5% than for 1.5% limonene …”
Section: Introductionmentioning
confidence: 61%
“…Crystallization kinetics experiments also showed that the parameters , , and changed throughout the fermentation process for all temperatures tested; i.e., the rate constant was reduced, causing to increase, hence a slower CB crystallization process as the fermentation progressed. This behavior is due to the chemical composition of the cocoa bean, which changes throughout fermentation by the generation of other components that influence the crystallization behavior of CB [ 11 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to study the polymorphic transitions of the CB because they influence the properties of chocolate [ 61 ]. The stability and melting temperatures ( ) of the CB polyforms increase when they are transformed from γ to .…”
Section: Discussionmentioning
confidence: 99%
“…Limonene is a low-cost and readily available terpene with a variety of applications in different areas such as food and beverages [ 19 , 20 ], pharmaceutical [ 21 ], bio-solvent [ 22 ], cosmetics and personal care [ 23 , 24 ]. Limonene has also been used as a building block to prepare various types of biobased polymers [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%